Social Media User Perception on Communication Types: Comparing One-Two Way of Communicating Brand - Gunawan, Arie Indra; Monoarfa, Hilda; Hendrayati, Heny; Bahri, Khoirun Nisa; Rahayu, Agus; Huda, Miftakul (Journal of Marketing Innovation (JMI), 2023)
Social media is a communication medium expected to create brand satisfaction and trust. If we attempt to classify communication patterns and intensity on Instagram media, there are one- and two-way communication patterns. Some posts do not require confirmation, and the goal is not to create a conversation between the messenger and the audience. This condition creates a knowledge gap in marketing communications that need to be known empirically. This research was conducted with a quantitative approach - descriptive statistics. Research data was collected by distributing questionnaires through communication and sending messages to Instagram accounts. 249 data are obtained and analyzed using Warp-PLS. The research findings show that one-way communication patterns are more effective in creating brand trust. The audience considers information conveyed in this pattern more effective and valid because they are not distracted by multi-respondent conversations, which often extend from information topics. This study has implications for theoretical contributions to creating brand satisfaction and trust and for the company's communication strategy to deliver brand communications to the audience. Also, companies can vary their communication patterns on social media, especially Instagram, from the audience that continues to respond (further conversations occur).